Dual-layer zirconia-kaolin hollow fibre in membrane contactor for ammonia recovery - Pauzan, Mohammad Arif Budiman (2022)
This study was initiated to develop of a green technology in ammonia recovery by using ceramic membrane derived from natural ceramic material in membrane contactor (MC) system. The main objective of this study is to develop a high performance and superhydrophobic dual-layer ceramic hollow fibre membranes for effective ammonia recovery from alternative natural material, Malaysian kaolin. However, due to high content of silica in kaolin which dissolves in high concentration of ammonia has hindered it to be used in MC system which requires high concentration of ammonia to work efficiently. Hence, a range of zirconia was added in this work to tackle the problem. Plus, the fabrication of dual layer configuration to the membrane by creating a protecting layer to the mixed zirconia-kaolin membrane enhanced the performance of the membrane in high concentration of ammonia. The dual-layer mixed zirconia-kaolin hollow fibre membrane (DLZK) was fabricated by using single step co-extrusion phase inversion/co-sintering technique where the mixed zirconia-kaolin was on the inner layer while zirconia was only on the outer layer. Upon investigation on the effect of different co-sintering temperatures, DLZK co-sintered at 1300°C showed the best characteristics in term of high mechanical strength (116 MPa) and possessed low dissolution rate in high alkaline solution. Finally, prior to be used in MC application system, the surface of the membranes was modified to be hydrophobic by grafting with fluoroalkylsilane agent. Then, the membranes were subjected to MC operating system for ammonia recovery using two different concentrations of synthetic ammonia (NH4OH), contacted with sulphuric acid and compared in term of properties between the membranes. DLZK was discovered to yield the highest mass transfer coefficient which was 3.77 x 10-5 Kms-1 at 10M (pH 11-13) of NH4OH and was able to recover almost 80%. Then, the DLZK membrane was subjected to recover ammonia in the treated palm oil mill effluent. The membrane showed similar performance using synthetic wastewater of NH4OH as almost 80% of ammonia was successfully recovered with mass transfer coefficient of 3.50 x 10-5 Kms-1. This indicates that the fabricated DLZK membrane can be applied in MC system for ammonia recovery as an alternative naturally based membrane which possesses superhydrophobic properties and is able to withstand high alkaline condition. The ammonia recovered was in the form of ammonium sulphate, ((NH4)2SO4) salt, which can be used as alternative fertilizer.